AGRI-ENVIRONMENTAL ASSESSMENT OF CONVENTIONAL AND ALTERNATIVE BIOENERGY CROPPING SYSTEMS PROMOTING BIOMASS PRODUCTIVITY - KERVROËDAN, Léa; HOUBEN, David; GUIDET, Julien; DENIER, Julia; DULAURENT, Anne-Maïmiti; MARRACCINI, Elisa; DELIGEY, Amandine; JOURNEL, Charlotte; LAMERRE, Justine; FAUCON, Michel-Pierre (Frontiers of Agricultural Science and Engineering, 2022)
● Agri-environmental assessment of food, feed and/or biogas cropping systems (CS). ● Four-year experiment for the agri-environmental assessment of two innovative CS. ● Biogas CS has equal soil returned biomass than food CS but higher exported biomass. ● Feed and biogas CS present higher biomass productivity, but higher CO 2 emissions. ● CO 2 emissions related to produced biomass are 26% (±5%) lower in biogas CS. Bioenergy, currently the largest renewable energy source in the EU (64% of the total renewable energy consumption), has sparked great interest to meet the 32% renewable resources for the 2030 bioeconomy goal. The design of innovative cropping systems informed by bioeconomy imperatives requires the evaluate of the effects of introducing crops for bioenergy into conventional crop rotations. This study aimed to assess the impacts of changes in conventional cropping systems in mixed dairy cattle farms redesigned to introduce bioenergy crops either by increasing the biomass production through an increase of cover crops, while keeping main feed/food crops, or by substituting food crops with an increase of the crop rotation length. The assessment is based on the comparison between conventional and innovative systems oriented to feed and biogas production, with and without tillage, to evaluate their agri-environmental performances (biomass production, nitrogen fertilization autonomy, greenhouse gas emissions and biogas production). The result showed higher values in the biogas cropping system than in the conventional and feed ones for all indicators, biomass productivity (27% and 20% higher, respectively), nitrogen fertilization autonomy (26% and 73% higher, respectively), methanogenic potential (77% and 41% higher, respectively) and greenhouse gas emissions (15% and 3% higher, respectively). There were no negative impacts of no-till compared to the tillage practice, for all tested variables. The biogas cropping system showed a better potential in terms of agri-environmental performance, although its greenhouse gas emissions were higher. Consequently, it would be appropriate to undertake a multicriteria assessment integrating agri-environmental, economic and social performances.